Spontaneous Ureterocolic Fistula between Nonfunctioning Kidney Transplant Ureter and Colon in Setting of Diverticulitis - Madison K. Krischak; Jeffrey R. Ord; Ashton A. Connor; Andrew S. Barbas (Case Reports in Transplantation)
Ureterocolic fistula is a rare condition that most commonly occurs in the setting of diverticular disease. The development of a ureterocolic fistula following kidney transplantation is even rarer, with no prior cases in the literature to our knowledge. We describe the case of a patient with three prior failed kidney transplants who developed a fistula between the sigmoid colon and nonfunctioning renal transplant ureter in the setting of diverticulitis.